Development characteristics and reactivation deformation mechanism of the Lumai landslide in Shannan City, Xizang - Haishan MA; Ruian WU; Wenbo ZHAO; Jibo WANG; Chang QI; Pan DENG; Yingjun LI (Zhongguo dizhi zaihai yu fangzhi xuebao)
The complex geological conditions of the Tibetan Plateau have historically fostered the development of numerous ancient landslides. In recent years, the reactivation of these landslides has exhibited a concerning escalation, driven by extreme weather events and human activities, thereby posing significant hazards. This study examines the Lumai ancient landslide in Shannan City, Xizang, employing a combination of field geological investigation, drone mapping, numerical simulation, and other technical methodologies. The research focuses on analysing the reactivation characteristics and influencing factors, specifically investigating the reactivation mechanism of the ancient landslide under the effects of surface water infiltration and loading. The results indicate that the Lumai ancient landslide has a volume of 2.5×106 to 15.1×106 m3. The maximum height difference between the landslide’s leading edge shear outlet and the Dangxuxiongqu River at the slope foot exceeds 200 meters, with the deepest sliding zone located at the interface between bedrock and loose deposits. Deformation is primarily concentrated in the front part of the landslide’s accumulation zone, characterized by numerous cracks and steep scarps. The reactivation is significantly influenced by surface water infiltration and overloading. Under concentrated water infiltration, localized sliding frequently occurs at the landslide front. Additionally, increased loading at the front leads to overall deformation and a tendency toward high-position shear failure. These findings enhance the understanding of reactivation mechanisms for ancient landslides in the Shannan City, Xizang, and provide valuable insights for local disaster prevention and mitigation efforts.